Komunikasi Terapeutik Pada Masalah Remaja Yang Mengalami Kekerasan Seksual: Komunikasi Terapeutik Pada Remaja Yang Mengalami Kekerasan Seksual - Zahra, Alfina Putri; Agustia, Dini; Sujana, Dede Yusuf; Lestari, Seika Linda; Patimah, Papat (Ruang Ide Publisher, 2024)
Sexual violence among adolescents is any form of coercion or threat to engage in sexual activity. Sexual activity includes groping, sexual immorality and even cheating. Objective: This literature study aims to understand the effectiveness of therapeutic communication regarding problems in adolescents who experience sexual violence. Method: The method Using literature studies with narrative methods from research results published in 2013-2022. Literature search using strategies with keywords Therapeutic Communication After the Problem of Adolescents Experiencing Sexual Violence with the Google Scholer data base. Results: The results of this study revealed that the provision of therapeutic communication in adolescents who experience sexual violence can improve the quality of life. Conclusion: In this case, mentoring and counseling can help victims of sexual violence in overcoming the traumatic impact of the violence. Counselors and escorts must have good therapeutic communication skills and pay attention to the stages of implementing therapeutic communication, so as to help victims feel protected and get healing.